2005
DOI: 10.1007/s10549-005-1412-6
|View full text |Cite
|
Sign up to set email alerts
|

No adverse effects of adjuvant chemotherapy on hippocampal volumein Japanese breast cancer survivors

Abstract: We investigated the adverse effects of adjuvant chemotherapy on the hippocampus in Japanese breast cancer survivors with (n=44) and without (n=31) adjuvant chemotherapy. There were no significant differences in hippocampal volume (magnetic resonance imaging) or additionally in memory function (Wechsler Memory ScaleRevised) between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 15 publications
6
47
0
2
Order By: Relevance
“…This is in line with the absence of large differences between chemotherapyexposed survivors and the general population more than 20 years post-treatment that we observed. The only other study that investigated the association between hippocampal volume and chemotherapy did also not observe a relationship between the two [8]. Of all studies that investigated the effect of chemotherapy on brain structure, none examined total tissue volumes after cytotoxic treatment [2][3][4][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the absence of large differences between chemotherapyexposed survivors and the general population more than 20 years post-treatment that we observed. The only other study that investigated the association between hippocampal volume and chemotherapy did also not observe a relationship between the two [8]. Of all studies that investigated the effect of chemotherapy on brain structure, none examined total tissue volumes after cytotoxic treatment [2][3][4][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…This was not observed in another group of patients who were 3 years post-treatment [7]. A study that strictly examined hippocampal volume did not find differences between cancer patients who received chemotherapy 3 years before and those who did not [8]. We recently showed that breast cancer survivors who completed high-dose chemotherapy almost 10 years before had less focal gray matter than survivors who never received chemotherapy [4].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Gray and white matter volume loss as well as hippocampal atrophy have been described in association with some chemotherapeutic treatments (Schneiderman 2004;Saykin et al 2003;Madhyastha et al 2002). However, these findings have not always been replicated (Yoshikawa et al 2005) suggesting the need for further investigation.…”
Section: Neuroimaging and Neurophysiologic Correlates Of Chemotherapymentioning
confidence: 99%
“…30,31 Although the first study did not find any significant chemotherapy-related difference in hippocampal volume, 30 volume differences in the cingulate gyrus, superior and middle frontal gyri, parahippocampal gyrus and precuneus were observed at one (but not three) years. There is also a fascinating and rare, study of twins.…”
Section: Neuroimaging Studiesmentioning
confidence: 88%